Theoretical insights of catalytic oxidation of Hg0 on g-C3N4-supported Fe/Co/Ni-based bi-metallic catalysts using O2 in coal-fired flue gas as the oxidant. (15th December 2021) - Liu, Shuai; Xu, Mengxia; Pang, Chengheng; Lester, Edward; Wu, Tao
Graphical abstract: Highlights: Catalytic oxidation of Hg 0 on pristine and O pre-adsorbed dimer sites is studied. Hg 0 oxidation starts from the adsorption of O2 and its subsequent dissociation. Rate-determining step on Fe2 @g-C3 N4 and Co2 @g-C3 N4 is the cleavage of metal-O bond. HgO desorption step dominates the pristine and O-adsorbed Ni2 @ g- C3 N4 . Ni2 @ g- C3 N4 exhibited the highest efficiency in the catalytic oxidation of Hg 0 . Abstract: In this work, density functional theory (DFT) calculations were conducted to investigate the adsorption and oxidation of Hg 0 with O2 as the oxidant on pristine and O-adsorbed dimers of Fe, Co and Ni supported on the buckled g- C3 N4 surface. The calculation reveals that all the dimers supported on the buckled g- C3 N4 surface (Fe2 /Co2 /Ni2 @ g -C3 N4 ) are stable at 700 K. It is found that Hg 0 oxidation starts from the adsorption of O2 and its subsequent dissociation, followed by the formation of OHgO and the desorption of HgO from the surface. However, after desorption of the first HgO, the active site of the dimer becomes an O-adsorbed dimer, which affects - Hg 0 oxidation reaction although the reaction pathway is similar. DFT calculations demonstrate that both the pristine dimer and O-adsorbed dimer are effective in O2 dissociation and are relatively easy for the metal-O bond to break, which is associated with a low energy barrier for these two processes. However, the interactions between O2 /Hg 0 and the pristine surface are significantly stronger than those between O2 /Hg 0 and the O-adsorbed dimer site. Rate-determining step of catalytic oxidation process on the pristine and O-adsorbed Fe2 @g-C3 N4 and Co2 @g-C3 N4 is the cleavage of the metal-O bond, while the HgO desorption dominates the pristine and O-adsorbed Ni2 @ g- C3 N4 with an energy barrier of 2.04 eV and 1.62 eV, respectively. It is found that among the dimers studied, the Ni2 @ g- C3 N4 exhibites the highest efficiency in the catalytic oxidation of Hg 0 .